Some properties for integro-differential operator defined by a fractional formal - Abdulnaby, Zainab E.; W. Ibrahim, Rabha; Kilicman, Adem (SpringerOpen, 2016)
Recently, the study of the fractional formal (operators, polynomials and classes of special functions) has been increased. This study not only in mathematics but extended to another topics. In this effort, we investigate a generalized integro-differential operator